Tribological Behavior of Boronized Fe40Mn20Cr20Ni20 High-Entropy Alloys - Xin Guo; Xi Jin; Xiaohui Shi; Huijun Yang; Min Zhang; Junwei Qiao (Metals, 2021)
The tribological behavior of hot-rolled and boronized Fe40Mn20Cr20Ni20 high-entropy alloys (HEAs) sliding against a Si3N4 ball was investigated in the air, deionized water and seawater. The results showed that the hot-rolled Fe40Mn20Cr20Ni20 HEA was composed of an FCC (face-centered cubic) phase. In addition, the boronized HEA was composed of a great number of borides, including CrB, FeB, MnB, Fe2B, Fe3B and MnB2. The hardness increased from 139 HV to 970 HV after boronizing. In air, the wear rate decreased from 4.51 × 10−4 mm3/Nm to 0.72 × 10−4 mm3/Nm after boronizing. The wear mechanism transformed from abrasive wear and oxidative wear to the polishing effect. After boronizing, in the deionized water, the wear rate decreased from 1.27 × 10−4 mm3/Nm to 8.43 × 10−5 mm3/Nm. The wear mechanism transformed from abrasive wear and delamination wear to delamination wear. In the seawater, the wear rate decreased by about ten times that of hot-rolled alloy.